One-stage En bloc resection of thoracic spinal chondrosarcoma with huge paravertebral mass through the single posterior approach by dissociate longissimus thoracis - Xu, Wei; Ye, Chen; Zhang, Dan; Wang, Peng; Wei, Haifeng; Yang, Xinghai; Xiao, Jianru (Frontiers in Surgery, 2022)
Objective: To describe the details and outcomes of 3-D printing model-guided en bloc resection of CHS with huge paravertebral mass via the combined posterior median and Wiltse approach. Background: Total en bloc spondylectomy is conventionally based on the single posterior approach or combined anterior-posterior approach. However, the single posterior approach imposes a high technical demand on the surgeon due to the narrow field of vision, limited surgical space and the delicate spinal cord, while the combined anterior-posterior approach not only requires greater patient tolerance but is time consuming and runs the risk of more blood loss and injury to the visceral pleura and large blood vessels during surgery. In addition, it is difficult to completely remove the thoracic CHS with paravertebral mass through simple en bloc resection when it involves the aorta, vena cava, costa and lung. Methods: Between 2010.08 and 2016.01, we performed a retrospective study to evaluate the clinical characteristics and outcomes of en bloc resection of thoracic spinal CHS with paravertebral mass through the combined posterior median and Wiltse approach. Postoperative recurrence-free survival (RFS) and overall survival (OS) were estimated by the Kaplan-Meier method. P ≤ 0.05 were considered statistically significant. Results: Altogether 15 patients received en bloc resection of thoracic spinal CHS with paravertebral mass through the combined posterior median and Wiltse approach. The mean age was 37.0 ± 12.8 years (median 36; range 15-64). This combination approach provided more extensive exposure and wider marginal resection of the tumor within a mean operation duration of 288 ± 96 min (median 280; range 140-480) and mean intraoperative blood loss of 1966 ± 830 ml (median 2000; range 300-3000). 5 patients experienced local recurrence of the disease; the mean time from surgery to recurrence was 22 ± 9.85 months (median 17, range 13-35). RFS in patients with recurrent CHS was significantly lower than that in patients with primary CHS on admission (P = 0.05). Conclusions: The combined posterior median and Wiltse approach is a technically viable option for en bloc resection of thoracic spinal CHS with huge paravertebral mass, and can give a favorable local control of CHS.